2014
DOI: 10.1086/677161
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Strategies to Reduce Blood Culture Contamination in the Emergency Department: Sterile Collection Kits and Phlebotomy Teams

Abstract: Objective Blood culture collection practices that reduce contamination, such as sterile blood culture collection kits and phlebotomy teams, increase upfront costs for collecting cultures but may lead to net savings by eliminating downstream costs associated with contamination. The study objective was to compare overall hospital costs associated with three collection strategies: usual care, sterile kits, and phlebotomy teams. Design Cost analysis. Setting This analysis was conducted from the perspective of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 21 publications
(41 reference statements)
3
47
1
Order By: Relevance
“…Using a fully sterile procedure with a standardized kit that contained sterile gloves and with a large fenestrated drape to create a sterile field resulted in relative decreases of 43% and 64% at 2 EDs 79 A recent cost analysis based on the 2013 study by Self et al compared 3 strategies: usual care in which nurses collected BCs without a standardized protocol, use of kits containing sterile gloves and drapes, or use of phlebotomy teams. 80 Based on a BCC rate of 1.68% when using a sterile kit, the authors determined that the annual savings were $483,219. The strategy of using sterile kits was less costly than usual care.…”
Section: Prepackaged Kitsmentioning
confidence: 99%
“…Using a fully sterile procedure with a standardized kit that contained sterile gloves and with a large fenestrated drape to create a sterile field resulted in relative decreases of 43% and 64% at 2 EDs 79 A recent cost analysis based on the 2013 study by Self et al compared 3 strategies: usual care in which nurses collected BCs without a standardized protocol, use of kits containing sterile gloves and drapes, or use of phlebotomy teams. 80 Based on a BCC rate of 1.68% when using a sterile kit, the authors determined that the annual savings were $483,219. The strategy of using sterile kits was less costly than usual care.…”
Section: Prepackaged Kitsmentioning
confidence: 99%
“…These are best characterized for false positive (contaminated) blood cultures, and are likely in excess of $10,000 per patient with false positive results. 20 Thus, our estimated direct cost calculations may substantially underestimate the true costs associated with indiscriminant microbiological testing. …”
Section: Discussionmentioning
confidence: 95%
“…4,5 Several authors have shown the deleterious consequences of false-positive BCs because they induce further testing and prolong hospital stay. [13][14][15][16][17][18][19] It has been estimated that each false positive result carries an economic burden of $4.385-$8.720 when those patients are compared with patients without positive BC. 13,14 It is also possible that the unnecessary use of antibiotic agents in these patients could be a contributor to the genesis of antibiotic resistance in hospital settings.…”
Section: Discussionmentioning
confidence: 99%
“…13,15,17,18 BC contamination rate reduction has been the focus of several studies conducted in adult and pediatric hospital populations, as well as in emergency services. Education-based interventions, [22][23][24] campaigns to encourage handwashing, 21 the appointment of dedicated phlebotomists to collect samples, 19,25 the prohibition of the use of venous catheters as a source of blood, 14,25,26 and the use of special kits for blood extraction 19,24 have shown positive results. However, in studies of critical care unit patients only the effect of the use of central venous lines as a source of BC have been examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation